WSL5, a pentatricopeptide repeat protein, is essential for chloroplast biogenesis in rice under cold stress - Liu, Xi (J Exp Bot, 2018)
Chloroplasts play an essential role in plant growth and development, and cold conditions affect chloroplast development. Although many genes or regulators involved in chloroplast biogenesis and development have been isolated and characterized, many other components affecting chloroplast biogenesis under cold conditions have not been characterized. Here, we report the functional characterization of a white stripe leaf 5 (wsl5) mutant in rice. The mutant develops white-striped leaves during early leaf development and is albinic when planted under cold stress. Genetic and molecular analysis revealed that WSL5 encodes a novel chloroplast-targeted pentatricopeptide repeat protein. RNA sequencing analysis showed that expression of nuclear-encoded photosynthetic genes in the mutant was significantly repressed, and expression of many chloroplast-encoded genes was also significantly changed. Notably, the wsl5 mutation causes defects in editing of rpl2 and atpA, and splicing of rpl2 and rps12. wsl5 was impaired in chloroplast ribosome biogenesis under cold stress. We propose that the WSL5 allele is required for normal chloroplast development in maintaining retrograde signaling from plastids to the nucleus under cold stress.